2021
DOI: 10.1093/cid/ciaa1912
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Testing for Respiratory and Gastrointestinal Shedding of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Day Care Centers in Hesse, Germany

Abstract: Background With the pandemic of SARS-CoV-2 ongoing in Europe in June of 2020, day care centres were reopened in the state of Hesse, Germany, after the lockdown. The role young children play in the dynamics of the transmission was unknown. Methods We conducted a longitudinal study over a period of 12 weeks and two days (18 th of June 2020 to 10 th of September, 2020) to screen attendees and staff from day care centres in the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Several reports have assessed the role of children in the dynamics of SARS-CoV-2 transmission. A study conducted in day care centers in Germany that used buccal mucosal and anal swabs for SARS-CoV-2 detection concluded that day care centers are not relevant reservoirs in a low prevalence setting (12). However, this study used self-testing, lacked oropharyngeal swab specimens, and was conducted during a minimal local incidence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have assessed the role of children in the dynamics of SARS-CoV-2 transmission. A study conducted in day care centers in Germany that used buccal mucosal and anal swabs for SARS-CoV-2 detection concluded that day care centers are not relevant reservoirs in a low prevalence setting (12). However, this study used self-testing, lacked oropharyngeal swab specimens, and was conducted during a minimal local incidence rate.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the first pandemic year, children were reported to be less likely to become infected with SARS-CoV-2 compared to adults and elderly. For infants, the reported number of cases were even lower (2)(3)(4).…”
Section: Introductionmentioning
confidence: 93%
“…While children of kindergarten age rarely have severe disease when infected with SARS-CoV-2 1-3 measures of public health, such as distancing and wearing of masks, cannot be applied to the same extend in day care centers as in other educational facilities. Nevertheless, a growing body of evidence suggested a limited role of day care centers in community spread of wild type SARS-CoV-2 in Central Europe in 2020 and early 2021 [4][5][6][7][8] . However, some of these studies were conducted during low community activity 4,5 , limiting the transferability to a setting with increased community spread.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence suggested a limited role of day care centers in community spread of wild type SARS-CoV-2 in Central Europe in 2020 and early 2021 [4][5][6][7][8] . However, some of these studies were conducted during low community activity 4,5 , limiting the transferability to a setting with increased community spread. One of these studies was the SAFE KiDS study, which we conducted in the summer of 2020 in 50 day care centers in the state of Hesse, Germany 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation